Whole-genome surveillance identifies markers of Plasmodium falciparum drug resistance and novel genomic regions under selection in Mozambique - Erin Coonahan; Hunter Gage; Daisy Chen; Emilia Virginia Noormahomed; Titos Paulo Buene; Irina Mendes de Sousa; Kevan Akrami; Lucia Chambal; Robert T. Schooley; Elizabeth A. Winzeler; Annie N. Cowell (mBio, 2023)
ABSTRACT The emergence of Plasmodium falciparum drug resistance threatens the efficacy of antimalarial therapies globally. Population genomic studies have been instrumental in mapping malaria genes associated with drug resistance. However, to understand the impact of regional malaria control strategies on the malaria genome, it is necessary to examine parasite subpopulations at the country level. Here, we use selective whole-genome amplification (SWGA) to analyze 120 samples from patients with severe malaria in Mozambique, a country with high malaria burden and risk of emerging drug resistance. We demonstrate that SWGA allows for the generation of near-complete whole-genome sequences from clinical P. falciparum isolates. Our analysis shows that Mozambique parasite genomes show strong diversification of vaccine targets including the circumsporozoite protein (csp), the target of the RTS,S vaccine. Parasites in this population appear fully sensitive to chloroquine, bearing no likely resistance conferring mutations in the chloroquine resistance transporter, pfcrt (PF3D7_0709000) and highly resistant to sulfadoxine-pyrimethamine, exhibiting resistant haplotypes at near fixation. Despite a long history of artemisinin use in Mozambique, we find no evidence of selection near pfkelch13 (PF3D7_1343700) nor evidence of artemisinin resistance conferring mutations in pfkelch13. Using identity by descent analysis, we show positive selection at genomic regions on chromosomes 6, 8, 12, 13, and 14. Gene candidates within these regions include the amino acid transporter 1 (pfaat1, PF3D7_0629500) on chromosome 6 which bears an S258L substitution in >80% of parasites, and a region on chromosome 14 previously amplified under artemisinin pressure. IMPORTANCE Malaria is a devastating disease caused by Plasmodium parasites. The evolution of parasite drug resistance continues to hamper progress toward malaria elimination, and despite extensive efforts to control malaria, it remains a leading cause of death in Mozambique and other countries in the region. The development of successful vaccines and identification of molecular markers to track drug efficacy are essential for managing the disease burden. We present an analysis of the parasite genome in Mozambique, a country with one of the highest malaria burdens globally and limited available genomic data, revealing current selection pressure. We contribute additional evidence to limited prior studies supporting the effectiveness of SWGA in producing reliable genomic data from complex clinical samples. Our results provide the identity of genomic loci that may be associated with current antimalarial drug use, including artemisinin and lumefantrine, and reveal selection pressure predicted to compromise the efficacy of current vaccine candidates.